Measuring Wages and Inequality in South Africa Using Two Nationally Representative Data Series - McDougall, Bruce (School of Economics, 2019)
The National Income Dynamics Study (NIDS) and the Post-Apartheid Labour Market Series (PALMS) are two data sources frequently relied upon for research into earnings in South Africa. This paper contributes to the literature in three ways. Firstly, I show how NIDS data can be adjusted to account for item non-response using a bracket reweighting technique and the effects thereof. Secondly, I consider how estimates of the wage distribution differ between NIDS and PALMS when using the most comparable estimation methods available. Finally, I discuss what the data reveal about the evolution of inequality in South African wages between 2008 and 2014.